Systemic Diseases Associated with Retinal Dystrophies. (November 2014) - Werdich, Xiang Q.; Place, Emily M.; Pierce, Eric A.
Abstract Inherited retinal degeneration (IRD) may occur in isolation or as part of a multi-systemic condition. Ocular manifestations may be the presenting symptom of a syndromic disease and can include retinitis pigmentosa, cone-rod dystrophy, or maculopathy. Alternatively, patients affected with syndromic disease may already have other systemic manifestations at the time retinal disease is diagnosed. Some of these systemic diseases can cause significant morbidity. Here, we review several of these syndromic IRDs and their underlying genetic causes. Early recognition and referral for systemic evaluation and surveillance may lead to early intervention and an improved outcome. Obtaining a molecular diagnosis can be beneficial in securing a definitive diagnosis, especially in cases with atypical presentations. A genetic diagnosis may also be informative with regard to prognosis and potential therapies. Effective management and rehabilitation for patients with syndromic retinal dystrophy requires a comprehensive genetic-based team approach involving patients, family members, ophthalmologists, primary care physicians, and geneticists.